Pencemaran Nama Baik dalam Perspektif Hukum Islam - Zuman Malaka (TARUNALAW Journal of Law and Syariah, 2026)
Defamation is an act that attacks a person's honor and dignity, a practice that has become increasingly prevalent with advances in information technology and social media. From an Islamic legal perspective, defamation is viewed as a reprehensible act, falling under the category of slander and insult, as it not only harms the individual but also threatens social harmony and order. This study aims to examine the definition of defamation, the legal basis for defamation in Islam, forms of defamation in the digital era, sanctions for perpetrators according to Islamic law, and prevention efforts. The method used is a normative study with a conceptual and normative juridical approach through sources of the Qur'an, hadith, and Islamic legal literature. The study shows that Islam strictly prohibits all forms of defamation, whether verbally, in writing, or digitally, and provides for sanctions in the form of qadzaf and ta'zir crimes. Furthermore, Islamic law emphasizes the importance of prevention through moral development, the principle of tabayyun (religious defamation), and social responsibility to uphold human dignity and achieve a just and harmonious society.